Real Shock, Monetary Aftershock: The 1906 San Francisco Earthquake and the Panic of 1907 - Kerry Odell; Marc D. Weidenmier (Claremont McKenna College, Department of Economics, 2001)
The Panic of 1907 is an important episode in American financial history because it led, in part, to the creation of the Federal Reserve. Although much has been written about the crisis, little has been said about its underlying causes. This study identifies the San Francisco earthquake and its subsequent conflagration as the proximate cause of the panic. London fire-houses insured San Francisco during this period. The payment of claims by British insurance companies following the quake and fire produced a large capital outflow in the fall of 1906, forcing the Bank of England to nearly double interest rates and discriminate against US trade bills. These actions pushed the US into a recession and made markets vulnerable to shocks that otherwise would have been transitory in nature. World financial markets crashed in October 1907 with the collapse of the Knickerbocker Trust Company in New York.
Keywords: 330